Estudio para determinar el nivel de aceptación productos alimenticios listos para calentar y servir en la ciudad de Manizales (2015)
Most of the foods that are usually part of our diet are the result of a series of more or less intense manipulations of food products, in order to ensure their hygiene, improve their organoleptic qualities (those we appreciate by the senses: color, aroma, flavor, texture) and to facilitate the consumer's preparation and consumption. The list of pre-cooked, prepared or refrigerated foods is increasing as well as its consumers. In this way, a few years ago several Colombian and foreign companies have been entering a new market that shows itself as potential and developing: the market for precooked and ready-to-serve foods. The reason why people consume these foods is not only their practicality but also their nutritional conditions and the time savings in their preparation. Under this scenario, the present research seeks to establish the viability of a food business ready to heat and serve, taking as a point of reference the degree of acceptance of the average stratum consumers of the city of Manizales towards foods ready to heat and serve In order to achieve this objective, the general characteristics of the food product to be investigated will be defined, and the level of acceptance of the food product ready to be heated and served will be analyzed. Finally, from the results found, possible strategies will be considered. would make viable the development of a business in this branch. It is important to mention that for the business administrator, entrepreneurship should be a guiding principle within their profession, so that any entrepreneurial activity is understood within the framework of "radical and discontinuous change management, or strategic renewal,   regardless of whether this strategic renewal occurs within or outside existing organizations, and regardless of whether or not this renewal gives rise to the creation of a new business entity. "1 In this way, the present research is also intended to describe an entrepreneurial entrepreneurship experience, based on the use of appropriate tools and strategies to detect potential markets.